To simplify the expression \((2x + 2) - (3x + 11)\), we first distribute the \(-1\) to each term in the second parentheses:
\[ (2x + 2) - (3x + 11) = 2x + 2 - 3x - 11 \]
Now, we combine like terms:
- Combine the \(x\) terms: \(2x - 3x = -x\)
- Combine the constant terms: \(2 - 11 = -9\)
Putting it all together, we have:
\[ -x - 9 \]
Now, we can select the two expressions that are equivalent to \(-x - 9\):
- \(-x - 9\)
- The expression \(2x - 3x + 2 - 11\) simplifies to \(-x - 9\) as shown below:
- \(2x - 3x = -x\)
- \(2 - 11 = -9\)
- So, \(2x - 3x + 2 - 11 = -x - 9\)
Therefore, the two equivalent expressions are:
- \(-x - 9\)
- \(2x - 3x + 2 - 11\) (which simplifies to \(-x - 9\))